Cleavage of Hsp70.1 causes lysosomal cell death under stress conditions - Yamashima, Tetsumori; Mochly-Rosen, Daria; Wakatsuki, Soichi; Mizukoshi, Eishiro; Seike, Takuya; Larus, Isabel Maria; Chen, Che-Hong; Takemura, Miho; Saito, Hisashi; Ohashi, Akihiro (Frontiers in Molecular Biosciences, 2024)
Autophagy mediates degradation of intracellular macromolecules and organelle within lysosomes. There are three types of autophagy: macroautophagy, microautophagy, and chaperone-mediated autophagy. Heat shock protein 70.1 (Hsp70.1) exhibits dual function as a chaperon protein and a lysosomal membrane stabilizer. Since chaperon-mediated autophagy participates for recycling of ~30 % cytosolic proteins, its disorder causes cell susceptibility to stress conditions. Cargo proteins destined for degradation like amyloid precursor protein, tau protein, etc., are trafficked by Hsp70.1 from the cytosol into lysosomes. Hsp70.1 is composed of N-terminal nucleotide-binding domain (NBD) and C-terminal domain that binds cargo proteins, termed substrate-binding domain (SBD). NBD and SBD are connected by the interdomain linker LL1 which modulates the allosteric structure of Hsp70.1 in response to ADP/ATP binding. After the passage of Hsp70.1-cargo complex through the lysosomal limiting membrane, high-affinity binding of positively-charged SBD with negatively-charged bis(monoacyl)glycerophosphate (BMP) at the internal vesicular membranes activates acid sphingomyelinase to generate ceramide for stabilizing lysosomal membranes. As integrity of the lysosomal limiting membrane is critical to ensure cargo protein degradation within the acidic lumen, disintegration of the lysosomal limiting membrane is lethal to cells. After intake of high-fat diets, however, β-oxidation of fatty acids in mitochondria generates reactive oxygen species which enhance oxidation of membrane linoleic acids to produce 4-hydroxy-2-nonenal (4-HNE). In addition, 4-HNE is produced during heating linoleic acid-rich vegetable oils, and incorporated into the body via deep-fried foods. These endogenous and exogenous 4-HNE synergically causes an increase in its serum and organ levels to induce carbonylation of Hsp70.1 at Arg469, which facilitates its conformational change and access of activated μ-calpain to LL1. Therefore, cleavage of Hsp70.1 occurs prior to its influx into the lysosomal lumen, which leads to lysosomal membrane permeabilization/rupture. The resultant leakage of cathepsins is responsible for lysosomal cell death which would be one of the causative factors of lifestyle-related diseases.